From Flowers to Strategy: A Swot-Based Business Development Analysis of Queency Florist - Felisia Mayang Sari; Rita Mutiarni (Proceeding International Conference on Digital Education and Social Science, 2025)
Increasing competition in the creative industry requires florist businesses to adopt adaptive and sustainable development strategies. This study aims to analyze internal and external conditions and formulate business development strategies for Queency Florist using SWOT analysis integrated with the IFE, EFE, IE, and Grand Strategy matrices. A qualitative descriptive method was employed, with data collected through observation, in-depth interviews with the business owner, and documentation. The results indicate that Queency Florist’s main strengths lie in product quality, creative design, and customer service, while weaknesses are related to limited digital marketing and financial management. The IFE score of 2.57 and the EFE score of 2.86 place the business in Cell V of the IE matrix, suggesting a hold and maintain strategy. The Grand Strategy Matrix positions the firm in Quadrant II, indicating that market penetration and product differentiation are the most appropriate strategies. This study highlights the importance of strengthening internal capabilities and optimizing digital marketing to enhance competitiveness and business sustainability.